ISLAM DAN KAPITALISME - Khobir, Abdul (IAIN Pekalongan, 2010)
Market economy with its competence has support capitalism from its beginning to always expand internally and externally. The impact of it has change the world economy and also the third world (developing countries), by the economic booming, like the increase of immigration as the impact of economic activities, the rapid development of technology, especially in information, electronic, communication, and bio-technology, and the success of international champagne to globalize capitalism in economy. To face this, Islam responds by the concept that Islam does not let the social class exist and avoid the centralization of properties only among the few rich people as it is in the capitalism. Islam issues different economic mode based on the Islamic teachings of need fulfillment, partnership, helping each other, and not based on struggling and conflict between social classes.